2022
DOI: 10.3390/jcm11113067
|View full text |Cite
|
Sign up to set email alerts
|

Association between Intra-Arrest Blood Glucose Level and Outcomes of Resuscitation at the Emergency Department: A Retrospective Study

Abstract: Since current cardiac arrest guidelines do not address the benefit of blood glucose measurement, the ideal ranges and target of blood glucose (BG) levels during cardiac arrest to achieve a better result are warranted. We intended to investigate the associations between intra-arrest BG levels and outcomes of cardiac arrest resuscitation at the emergency department (ED). We conducted a retrospective observational study at a single university hospital. Cardiac arrest patients at the ED between 2017 and 2020 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…Overall, our current study contributes to the growing body of literature regarding the association between dextrose administration during CPR and resuscitation outcomes. Although earlier studies documented that a low intra-arrest blood glucose level was strongly correlated with poor outcomes [ 8 , 9 ], this study highlights that dextrose might not provide a significant additional benefit or harmful effect. The correction of hypoglycemia during cardiac arrest might not result in a better outcome, questioning the importance of dextrose administration during CPR.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Overall, our current study contributes to the growing body of literature regarding the association between dextrose administration during CPR and resuscitation outcomes. Although earlier studies documented that a low intra-arrest blood glucose level was strongly correlated with poor outcomes [ 8 , 9 ], this study highlights that dextrose might not provide a significant additional benefit or harmful effect. The correction of hypoglycemia during cardiac arrest might not result in a better outcome, questioning the importance of dextrose administration during CPR.…”
Section: Discussioncontrasting
confidence: 58%
“…Expected dextrose delivery in cardiac arrest is not advised since it is linked with increased neurologic morbidity and a worse likelihood of survival to hospital discharge [ 20 ]. Nonetheless, our previous study found that intra-arrest blood glucose levels less than 100 mg/dL were associated with a lower chance of sustained ROSC [ 9 ]. However, according to this study, administering dextrose might not increase the chance of ROSC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 350,000 individuals die from out-of-hospital cardiac arrest (OHCA) in the United States [1]. Despite significant advances in treatments such as rapid reperfusion, aggressive post-resuscitation care, and targeted temperature management (TTM), the rates of neurologically intact survival to hospital discharge remain alarmingly low, ranging from 6% to 9% [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%